Peranan World Wide Fund for Nature (WWF) dalam Konservasi Lingkungan di Indonesia Studi Kasus : Sebangau Conservation Project Taman Nasional Sebangau Kalimantan Tengah - Utari Dina Sari (HI 16 UMY 046, 2016)
*46 This paper discuss the role of WWF on environmental conservation in Sebangau National Park. Sebangau National Park is one of swampland area that should be conserved because of serious hydrological damage, encompass Mega Project Area, illegal logging and forest fires. The government took action by set Sebangau National Park become a national park which the environment should be conserved in 2004. The role of WWF on environmental conservation in Sebangau National Park as fasilitator and initiator and the principles of ethics environment as moral responsibility for nature and caring to nature. In addition, this paper analyzes the case using the concept of the role of NGO High Level partnership: grassroot development and deep ecology.